2023
DOI: 10.2147/jir.s433843
|View full text |Cite
|
Sign up to set email alerts
|

Increased Systemic Immune-Inflammation Index Was Associated with Type 2 Diabetic Peripheral Neuropathy: A Cross-Sectional Study in the Chinese Population

Jia Li,
Xing Zhang,
Yi Zhang
et al.

Abstract: Background: Systemic immune-inflammation index (SII), a novel inflammatory marker, has been demonstrated to be associated with type 2 diabetes mellitus (T2DM) and its vascular complications, however, the relation between SII and diabetic peripheral neuropathy (DPN) has been never reported. We aimed to explore whether SII is associated with DPN in Chinese population. Methods: A cross-sectional study was conducted among 1460 hospitalized patients with T2DM. SII was calculated as the platelet count × neutrophil c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In a study of 300 Type 2 DM patients on whether SII has a predictive value for diabetic nephropathy and cardiovascular diseases in patients with Type 2 DM, predictive SII values were found for cardiovascular diseases and diabetic nephropathy [28]. In a study investigating the relationship between SII and diabetic neuropathy in 1460 hospitalized type 2 DM patients in China, it was found that SII levels were significantly higher in patients with diabetic neuropathy [29]. In another study in which 584 patients with diabetic nephropathy (DN) due to Type 2 DM, Type 2 DM patients without DN, and a control group were investigated for the relationship between SII and DN, it was found that high SII levels were associated with DN [30].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 300 Type 2 DM patients on whether SII has a predictive value for diabetic nephropathy and cardiovascular diseases in patients with Type 2 DM, predictive SII values were found for cardiovascular diseases and diabetic nephropathy [28]. In a study investigating the relationship between SII and diabetic neuropathy in 1460 hospitalized type 2 DM patients in China, it was found that SII levels were significantly higher in patients with diabetic neuropathy [29]. In another study in which 584 patients with diabetic nephropathy (DN) due to Type 2 DM, Type 2 DM patients without DN, and a control group were investigated for the relationship between SII and DN, it was found that high SII levels were associated with DN [30].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 300 type 2 DM patients on whether SII has a predictive value for diabetic nephropathy and cardiovascular diseases in patients with type 2 DM, predictive SII values were found for cardiovascular diseases and diabetic nephropathy [ 31 ]. In a study investigating the relationship between SII and diabetic neuropathy in 1460 hospitalized type 2 DM patients in China, it was found that SII levels were significantly higher in patients with diabetic neuropathy [ 32 ]. In another study in which 584 patients with diabetic nephropathy (DN) due to type 2 DM, type 2 DM patients without DN, and a control group were investigated for the relationship between SII and DN, it was found that high SII levels were associated with DN [ 33 ].…”
Section: Discussionmentioning
confidence: 99%